Use of a preprinted sticker to improve the prescribing of prophylactic antibiotics for hip fracture surgery. Issue 5 (1st October 2004) - Ritchie, S; Scanlon, N; Lewis, M; Black, P N
Abstract : Problem: Antibiotic prophylaxis has been shown to reduce the number of postoperative infections following surgery for hip fracture. At Auckland Hospital the policy for antibiotic prophylaxis for hip fracture surgery is for the patient to receive the first dose of antibiotic at the induction of anaesthesia followed by two more doses at 8 hour intervals. A previous audit found that patients often received too many doses of antibiotic. A retrospective audit was performed of 100 patients undergoing surgery for a hip fracture. The primary problem was over-prescribing; 68 patients (68%) received more than three doses. The number of patients who received three doses according to the guidelines was 29 (29%, 95% CI 21 to 40). Setting: Auckland Hospital which provides acute orthopaedic services for a population of 500 000. Strategy for change: A sticker was introduced with the prescription printed on it. The sticker was applied to the medication chart by the anaesthetist when the initial dose of antibiotic was given. Charts of a further 100 patients were reviewed after the introduction of the sticker and compared with those from another hospital in Auckland where the sticker was not used. Effects of change: The number of patients who received three doses, in accordance with the guidelines, improved to 74 (74%, 95% CI 64 to 82, p<0.001). These changes were observed even though the sticker was only used in 44 patients (44%, 95% CI 34 to 54). At the other hospital the number of patients who received three doses was 10 (20%, 95% CI 10 to 42) and 13 (26%, 95% CI 15 to 40, p = 0.37) for the same two periods. Lessons learnt: The use of a preprinted sticker is a simple intervention which improves the use of antibiotic prophylaxis at the time of surgery. This improvement occurred even though the sticker was used in slightly fewer than half the cases.